Analisis Perkembangan Motorik Halus Anak Usia Dini Melalui Kegiatan Bermaian Puzzle - Ni Nyoman Sandat; Luh Made Dwi Wedayanthi (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
Abstract: This study aims to analyze the development of fine motor skills in early childhood through puzzle-playing activities. Fine motor skills involve the coordination of small muscles, particularly those in the hands and fingers, which are essential for activities such as writing and drawing. The method used in this study was observation of children's puzzle-playing activities in kindergarten. The results indicate that playing puzzles significantly enhances children's fine motor abilities, including hand-eye coordination, the ability to grasp small objects, perseverance, and problem-solving. Children who frequently play with puzzles demonstrate improvements in their ability to assemble and complete puzzles quickly and accurately. Additionally, this activity helps improve children's focus and concentration. These findings suggest that puzzle games are not only enjoyable but also support the cognitive and motor development of early childhood.